2020
DOI: 10.1186/s12866-020-01920-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional probiotics of lactic acid bacteria from Hu sheep milk

Abstract: Background: Probiotics are being considered as valuable microorganisms related to human health. Hu sheep is referred as one of the important sheep breeds in China. Goat milk produced by Hu sheep is characterized with high nutritional value and hypoallergenic in nature. Particularly, this milk contains plenty of milk prebiotic and probiotic bacteria. This study was aimed to scrutinize more bacterial strains from Hu sheep milk with potential probiotic activity. Results: Based on 16S rRNA sequence analysis, pool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 58 publications
0
48
1
1
Order By: Relevance
“…Therefore, the use of safe, natural, and economic alternatives like the use of probiotics can be used to cope with these issues. Chen et al (2020) evaluated the safe status of Lactococcus lactis and Leuconostoc lactis strains and further examined the strains via in vitro tests for antimicrobial activity, cell surface characteristics, heat treatment, antibiotic susceptibility, and acid/bile tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of safe, natural, and economic alternatives like the use of probiotics can be used to cope with these issues. Chen et al (2020) evaluated the safe status of Lactococcus lactis and Leuconostoc lactis strains and further examined the strains via in vitro tests for antimicrobial activity, cell surface characteristics, heat treatment, antibiotic susceptibility, and acid/bile tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a combination of conventional screening and molecular biological identification is frequently used to comprehensively determine the type of probiotics from the morphological, biochemical and molecular levels. ( Chen et al, 2020 ) obtained P. pentosaceus with in vitro antibacterial effect from sow milk. They firstly inoculated sheep milk samples into a culture medium, followed by purification of the single-strain isolates using the repeated streaking method; and agar diffusion assay was then conducted to test antibacterial activity; following that, DNA isolation and PCR amplification were performed using the universal primers, and the strains were identified by 16S rDNA gene sequence homology analysis.…”
Section: P Pentosaceus Strain Screeningmentioning
confidence: 99%
“…Numerous studies confirmed that LAB had potential application value, including Pediococcus pentosaceus ( P. pentosaceus ). P. pentosaceus belongs to family Streptococcaceae , genus Pediococcus , and is a kind of LAB because it can produce lactic acid ( Chen et al, 2020 ). The individual of P. pentosaceus is spherical in pairs or quadruplets, and an immotile bacterium belonging to facultative anaerobic Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Although abundant probiotics have been isolated from human milk and bovine milk [10][11][12], strategies for the preservation and isolation of the natural bacteria of sow milk are limited currently. While culture-independent methods have allowed an understanding of the composition and diversity of sow milk microbiota [9], culturedependent methods are still critical for the functional identification and utilization of the sow milk microbiota, which might be indirectly or directly beneficial for precise care of early-weaning piglets.…”
Section: Introductionmentioning
confidence: 99%